Examining the impact of the 2007 Zaca Fire on the long-term hydrological recovery of the Santa Cruz Creek watershed in Southern California - Avery Walters; Nawa Raj Pradhan; Ian Floyd; Venkataraman Lakshmi (Journal of Hydrology: Regional Studies, 2025)
Study region: This study focuses on the Santa Cruz Creek watershed in Southern California, an area severely impacted by the 2007 Zaca Fire, which started on July 4, 2007, and was contained on September 4, 2007. The region is representative of wildfire-prone Mediterranean-climate catchments. Study focus: We assess long-term post-fire hydrological recovery using a novel dual approach: (1) simulating 16 storm events over a 23-year period (2001–2024) to evaluate pre-fire (2001–2007), post-fire (2007–2012), and recovery (2013–2024) conditions, and (2) directly comparing two similar storm events—one pre-fire (2006) and one during recovery (2017)—to isolate changes in watershed response. Hydrological modeling employed HEC-HMS with the Deficit and Constant Loss Method, the ModClark Transform Model, and the Linear Reservoir Baseflow Model. Remote sensing data, including Enhanced Vegetation Index (EVI) and SERVES Soil Moisture, enhanced modeling and analysis. New hydrological insights for the region: Vegetation cover, soil moisture, and several watershed parameters show substantial recovery after five years. EVI reached 84 % of pre-fire values, while initial soil moisture deficit, time of concentration, and storage coefficient each recovered to roughly 70 %. Fast baseflow exceeded pre-fire levels at 143 %, but slow baseflow declined to 20 %. Groundwater contributions recovered marginally to 52 %. Peak discharge and direct runoff volume declined from post-fire highs of 173 % and 136 % to 125 % and 84 % of pre-fire levels, respectively. Although vegetative conditions stabilize, watershed hydrology remains altered.